2017
DOI: 10.5625/lar.2017.33.3.223
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical safety assessment ofAngelica acutilobausing a 13-week repeated dose oral toxicity study in rats

Abstract: Angelica acutiloba (AA), a Japanese species of Danggui, has been used worldwide as a traditional herbal medicine with several bioactivities including anti-diabetic, anti-allergic, anti-inflammatory, anti-tumor, and anti-obesity. However, there is lack of toxicological data available to evaluate potential long-term toxicity and the no-observed-adverse-effect level (NOAEL) of AA extract in accordance with the test guidelines published by the Organization for Economic Cooperation and Development. In the 14-day re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…As a result, we showed that AAE at a dose of 800 mg/kg/day had some beneficial effects in HFD-fed SHRs. Yun et al [27] reported that no adverse effects were shown even at a dose of 2,000 mg/kg/day in the 13-week repeat-dose oral toxicity study in rat. Therefore, it is possible to use more amounts of AAE to obtain better results.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, we showed that AAE at a dose of 800 mg/kg/day had some beneficial effects in HFD-fed SHRs. Yun et al [27] reported that no adverse effects were shown even at a dose of 2,000 mg/kg/day in the 13-week repeat-dose oral toxicity study in rat. Therefore, it is possible to use more amounts of AAE to obtain better results.…”
Section: Discussionmentioning
confidence: 99%
“…5-Week old animals were purchased from Orient Bio Inc. (Gyeonggi-do, Korea) and only healthy animals were used in the study after two-week acclimation. As previously described [ 20 ], animals were housed in polycarbonate cages containing aspen bedding materials in an environment-controlled animal room at the AAALAC International-accredited animal facility (#001160) of Seoul National University Hospital. Animals were provided with sterilized laboratory rodent diet (LabDiet 5002, PMI Nutrition International) and autoclaved water at libitum .…”
Section: Methodsmentioning
confidence: 99%
“…5-Week old animals were purchased from Orient Bio Inc. (Gyeonggi-do, Korea) and only healthy animals were used in the study after two-week acclimation. As previously described [20], animals were housed in polycarbonate cages containing aspen bedding materials in an environment-controlled animal room at the AAAL AC International-accredited animal facility (#001160) [21]. Our toxicity studies were performed in compliance with the relevant OECD test guidelines [22][23][24][25][26] and Good Laboratory Practice regulations published by Korea Food Drug Administration [27].…”
Section: Animalsmentioning
confidence: 99%